Kierunki orzecznictwa w dziedzinie spraw dotyczących ochrony pracy - Jabłoński, Andrzej (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The article is devoted to the analysis of case law in matters related to health and safety at work. Case law in this area is very diverse and concerns very different problems. The study deals with the analysis of case law regarding the content and scope of the obligation to provide safe and hygienic working conditions, its legal nature, liability for violation of these obligations, including sanctions in the form of increasing social security contributions and termination of employment. The aim of the study was to capture the dominant tendencies in the case law and to present the dominant directions of its development. Of particular interest in this context is the tendency to recognize the responsibility of the employer for violation of the right to safe and healthy working conditions based on the concept of the protection of personal rights.
Keywords: liability; personal rights; contribution; right to safe and healthy working conditions; real safety at work